Combustion investigation of waste cooking oil (WCO) with varying compression ratio in a single cylinder CI engine. (1st January 2021) - Sahu, Tomesh Kumar; Sarkar, Sumit; Shukla, Pravesh Chandra
Highlights: Production of Waste Cooking Oil (WCO) based biodiesel by transesterification process. The physico-chemical properties for WCO biodiesel were measured. Effect of variation in compression ratio on combustion of WCO biodiesel was investigated. Ignition delay (ID), combustion phasing and combustion duration (CD) were investigated. Brake thermal efficiency and fuel consumption were determined. Abstract: Biodiesel is a popular alternative fuel of mineral diesel which is normally produced by using straight vegetable oils (SVO). Since the conversion of edible oils into biodiesel may affect its supply/availability as a food item, it is desirable to use non-edible oils for biodiesel production for a long time. Waste cooking oil (WCO) is one such non-edible oil, however superior in quality for biodiesel production through transesterification. The current study is mainly focused on the utilization of WCO as an alternative for mineral diesel in a typical agricultural compression ignition four stroke water-cooled engine. Effect of higher compression ratio (CR20) on various combustion and performance parameters such as in-cylinder pressure (P-θ), heat release rate (HRR), peak pressure (Pmax), maximum pressure rise rate (dP/dθ)max, combustion duration, combustion phasing etc. were investigated for WCO biodiesel and compared with mineral diesel. These experiments were performed for five different loading conditions (No load to full load) at 1500 rpm. Increase in compression ratio (CR) from 18 to 20 resulted in lower ignition delay for higher engine load condition which reduced by 6 CAD. Full load engine operation resulted in 32% brake thermal efficiency (BTE) for WCO biodiesel which was 18% higher than diesel. Peak in-cylinder pressures (Pmax) were observed similar for diesel and WCO biodiesel for same operating conditions except full load condition where it showed lower Pmax value. WCO biodiesel turned out to be more efficient with 6% lower BSFC for the full load operating conditions (CR20).